2018
DOI: 10.1007/s40263-018-0578-5
|View full text |Cite|
|
Sign up to set email alerts
|

A Phase I, Randomized, Double-Blind, Placebo-Controlled, Single Ascending Dose, Multiple Dose, and Food Effect Trial of the Safety, Tolerability and Pharmacokinetics of Highly Purified Cannabidiol in Healthy Subjects

Abstract: BackgroundA formal single ascending and multiple dose pharmacokinetic (PK) trial of cannabidiol (CBD) oral solution was required to determine the safety and tolerability of CBD, the maximum tolerated dose, and to examine the effect of food on CBD PK parameters.ObjectiveThis trial assessed the safety, tolerability and PK of CBD oral solution in healthy adult volunteers, as well as the effect of food on CBD PK parameters.MethodsThe study consisted of three arms: single ascending dose (1500, 3000, 4500 or 6000 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
372
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 337 publications
(425 citation statements)
references
References 20 publications
30
372
6
Order By: Relevance
“…With the exception of the higher incidence of rashes, the AE profile when cannabidiol was administered in combination with clobazam, stiripentol, or valproate is highly consistent with another cannabidiol trial in healthy volunteers and in recent phase 3 trials . In this healthy volunteer DDI trial, most AEs were mild, with 8 subjects reporting moderate and 2 reporting severe AEs.…”
Section: Discussionsupporting
confidence: 73%
“…With the exception of the higher incidence of rashes, the AE profile when cannabidiol was administered in combination with clobazam, stiripentol, or valproate is highly consistent with another cannabidiol trial in healthy volunteers and in recent phase 3 trials . In this healthy volunteer DDI trial, most AEs were mild, with 8 subjects reporting moderate and 2 reporting severe AEs.…”
Section: Discussionsupporting
confidence: 73%
“…CBD is reported to have a high apparent volume of distribution after oral dosing ( V / F ) ranging from 250 to 450 L/kg and a highly variable plasma oral clearance (CL/ F ) ranging from 533 to 3783 L/h . CBD half‐life ( t 1/2 ) ranges from 18 to 60 hours …”
Section: Introductionmentioning
confidence: 99%
“…Evidence exists for a large food effect with lower doses (approximately 40 mg single dose) of tetrahydrocannabinol (THC) and CBD (1:1) delivered as an oromucosal spray, resulting in a threefold higher C max and fivefold higher area‐under‐the‐concentration‐time curve (AUC 0‐∞ ) for fed compared to fasting states . A similar food effect for the currently approved FDA liquid formulation (Epidiolex) has also been reported . Liquid formulations are associated with a higher possibility of inconsistent dosing, which complicates the characterization of drug pharmacokinetics .…”
Section: Introductionmentioning
confidence: 99%
“…Few descriptive PK parameters of CBD, such as area under the concentration‐time curve (AUC), maximum concentration (Cmax), and time of Cmax (Tmax), have been reported, and a large variation in PK parameters was found among the study subjects . The large variability was partly explained by feeding status, as food intake has been shown to delay Tmax and increase AUC and Cmax . The various dosage forms also resulted in different PK profiles; for example, smoking or vaping CBD results in a shorter Tmax compared with other dosage forms .…”
mentioning
confidence: 99%
“…The various dosage forms also resulted in different PK profiles; for example, smoking or vaping CBD results in a shorter Tmax compared with other dosage forms . Additionally, other studies reported a less than proportional dose‐exposure relationship . The feeding status, dosage form, and dose contributed to CBD PK variability; however, their contributions were not well quantified.…”
mentioning
confidence: 99%